Richard Brome et la catharsis comique : théorie des semblables ou théorie des contraires ? - Athéna Efstathiou-Lavabre (Etudes Epistémè)
Richard Brome (1590 ?-1652) often nurtures the hope of curing his characters, such as Peregrine, Joyless, Oldrents and others. And since it is characters he hopes to cure, not people, it would be preferable to replace the term comic catharsis with an unquestionably more appropriate one, fictional comic catharsis. In this paper, then, it is fictional comic catharsis that I will analyse, the fictional component being demonstrated by the fact that Brome’s characters are cured in a fictional context, unlike true comic catharsis, whose effect on the actual audience remains highly speculative. With this in mind, I will touch briefly on the notion of catharsis as expounded by Aristotle in his Poetics, before considering the interpretation of the term by 16th and 17th century theorists, especially those on the continent. I then wish to consider the way in which fictional comic catharsis operates, through an analysis of Brome’s least neglected and, from a dramaturgical perspective, most accomplished comedy, The Antipodes (1636). And I will attempt to establish if it is similar to either of the two Hippocratic theories which are often seen as opposites, though perhaps they are complementary, that is, the theory of similitude and the theory of contraries.